All the single ladies: Job promotions and the durability of marriage - Olle Folke; Johanna Rickne (Research Institute of Industrial Economics (IFN), 2016)
This paper addresses women's under-representation in top jobs in organizational hierarchies. We show that promotions to top jobs dramatically increase women's probability of divorce, but do not affect men's marriages. This effect is causally estimated for top jobs in the political sector, where close electoral results deliver exogenous variation in promotions across job candidates. Descriptive evidence from job promotions to the position of CEO shows that private sector promotions result in the same gender inequality in the risk of divorce. A description of male and female job candidates' household formations sheds some light on the mechanism behind this result. For most male candidates for top jobs, their promotion aligns with the gender-specialized division of paid and unpaid labor in their households. Many female candidates for top jobs live in dual-earner households and are married to older husbands who take a small share of parental leave. Divorce among women in top jobs occurs more often in couples with a larger age gap and a less equal division of leave, and in households in which her promotion shifts the division of earnings (further) away from the norm of male dominance. No divorce effect is found in couples that are more gender-equal in terms of having a smaller age gap and a more equal division of parental leave. We argue that norms and behavior in the marriage market hinder the closure of the gender gap in the labor market.
Keywords: H00; J12; J16; 330; Promotions; Marriage; Social norms; Divorce; Career